Foreign Inputs and Changes in Domestic Value Added Exports: Empirical Evidence from Latin American Countries. - Assamoi, Guy Roland; Wang, Shaoyuan; Gnangoin, Yobouet Thierry Bienvenu; Edjoukou, Akadje Jean Roland (International Journal of Economics and Financial Issues, 2019)
This paper aims to analyze the factors affecting domestic value added in exports for seven Latin American countries (LAC) with a focus on the role played by foreign inputs. By using panel data (1995-2016) with fixed effects model, the paper finds that foreign value added (FVA) in exports is a strong determinant of positive changes in domestic value added exports in Latin America. The paper also finds that institutions, tariffs and labor productivity are important determinants of changes in DVA in exports. Additionally, a sectoral analysis reveals the positive effect of FVA in exports on changes in DVA in exports in three sectors: agriculture, manufacture and services. However, FVA in exports has no significant effect on DVA in exports in the mining sector. Overall, our results suggest countries to lower tariffs, to adopt policies that enhance the import of sophisticated intermediates inputs and to promote favorable business environment. Keywords: Value Added Exports, Global Value Chains, Latin America. JEL Classifications: F13, F14, N16, P33 DOI: https://doi.org/10.32479/ijefi.8059